Peningkatan Kualitas Bunga Telang Melalui Perbaikan Proses Pengeringan Menggunakan Metode Taguchi - Sukma Dwi Yuliana Puspitasari Sanggup; Said Salim Dahda (Jurnal Optimalisasi, 2022)
The use of Butterfly pea is widely used as a colorant in various local foods in Indonesia and Southeast Asian countries. This use is limited to foods that do not have a long shelf life. Processing and storage by drying in an effort to improve storage quality requires a special eksperimenal design to improve product quality. One of the eksperimenal designs that can be used is the Taguchi method. This research was conducted in Yosowilangun Village, Gresik Regency, there are problems that can be formulated in this study, namely "How is a good parameter setting of the factors that affect the quality in the drying process? ". This study uses the Taguchi method with 2 factors and 4 levels. The factors used are Temperature (A) and Drying Time (B). The temperature consists of 4 levels, namely 45⁰C (A), 50⁰C (B), 55⁰C (C), and 60⁰C (D). while the Drying Time consists of 4 levels, namely 30 Minutes (A), 60 Minutes (B), 90 Minutes (C), and 120 Minutes (D). The results showed that the determination of the optimal factor level was the one that obtained the smallest water content test results, which was obtained by setting the temperature factor at level 2 of 50⁰C (A2) and drying time at level 2 of 60 minutes (B2). While the decrease in the water content of the telang flower at the optimal level is 40%.